If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(9x + 12) + 2(12x + 9) = 24(6x + 3) Reorder the terms: 2(12 + 9x) + 2(12x + 9) = 24(6x + 3) (12 * 2 + 9x * 2) + 2(12x + 9) = 24(6x + 3) (24 + 18x) + 2(12x + 9) = 24(6x + 3) Reorder the terms: 24 + 18x + 2(9 + 12x) = 24(6x + 3) 24 + 18x + (9 * 2 + 12x * 2) = 24(6x + 3) 24 + 18x + (18 + 24x) = 24(6x + 3) Reorder the terms: 24 + 18 + 18x + 24x = 24(6x + 3) Combine like terms: 24 + 18 = 42 42 + 18x + 24x = 24(6x + 3) Combine like terms: 18x + 24x = 42x 42 + 42x = 24(6x + 3) Reorder the terms: 42 + 42x = 24(3 + 6x) 42 + 42x = (3 * 24 + 6x * 24) 42 + 42x = (72 + 144x) Solving 42 + 42x = 72 + 144x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-144x' to each side of the equation. 42 + 42x + -144x = 72 + 144x + -144x Combine like terms: 42x + -144x = -102x 42 + -102x = 72 + 144x + -144x Combine like terms: 144x + -144x = 0 42 + -102x = 72 + 0 42 + -102x = 72 Add '-42' to each side of the equation. 42 + -42 + -102x = 72 + -42 Combine like terms: 42 + -42 = 0 0 + -102x = 72 + -42 -102x = 72 + -42 Combine like terms: 72 + -42 = 30 -102x = 30 Divide each side by '-102'. x = -0.2941176471 Simplifying x = -0.2941176471
| (2xy^3)(6x^4)= | | (-6ab^2)(-9bc)= | | 23x^2-34x=0 | | (9ay)(-8y)= | | (5x^2y^3)(5x^2y^3)= | | 2+(3*w)=12+(2*w) | | (8b^3cd)(2b)= | | 15x^2-59x+56=0 | | (6a^5b^6)(3ab)= | | -(x+1)+2x-6=7 | | 17b=9.4 | | 3(2a+1)-5a=5-3 | | -2(x-6)+3x=7-9 | | 3(x+4)-2x=2 | | (9x^3+5x^2-4x)-(5x^3-2x^2-6x)-(4x^3+6x^2+24)=0 | | 9(-2-9a)-5=103-81a | | 4-8=6x-5x+9 | | X+5y=2x+38 | | 2t+3=21-4t | | 2a-5-a=-4+7 | | 17b-2=-7.4 | | (7m^2n^2)(m^6n^2)= | | 3a+6-2a=5 | | 7-4=a-3 | | (b^3df^3)(b^5d)= | | x-9+7=-5-8 | | 24x^2+160x-256=0 | | -16k=4 | | 17-x=1/3×21 | | x+8-3=2-7 | | 4k^2-12k-7=0 | | y+4.3=-7.7 |